Atmospheric vs. anaerobic processing of metabolome samples for the metabolite profiling of a strict anaerobic bacterium, Clostridium acetobutylicum. Issue 12 (10th September 2014) - Lee, Sang‐Hyun; Kim, Sooah; Kwon, Min‐A; Jung, Young Hoon; Shin, Yong‐An; Kim, Kyoung Heon
ABSTRACT Well‐established metabolome sample preparation is a prerequisite for reliable metabolomic data. For metabolome sampling of a Gram‐positive strict anaerobe, Clostridium acetobutylicum, fast filtration and metabolite extraction with acetonitrile/methanol/water (2:2:1, v/v) at −20°C under anaerobic conditions has been commonly used. This anaerobic metabolite processing method is laborious and time‐consuming since it is conducted in an anaerobic chamber. Also, there have not been any systematic method evaluation and development of metabolome sample preparation for strict anaerobes and Gram‐positive bacteria. In this study, metabolome sampling and extraction methods were rigorously evaluated and optimized for C. acetobutylicum by using gas chromatography/time‐of‐flight mass spectrometry‐based metabolomics, in which a total of 116 metabolites were identified. When comparing the atmospheric (i.e., in air) and anaerobic (i.e., in an anaerobic chamber) processing of metabolome sample preparation, there was no significant difference in the quality and quantity of the metabolomic data. For metabolite extraction, pure methanol at −20°C was a better solvent than acetonitrile/methanol/water (2:2:1, v/v/v) at −20°C that is frequently used for C. acetobutylicum, and metabolite profiles were significantly different depending on extraction solvents. This is the first evaluation of metabolite sample preparation under aerobic processing conditions for an anaerobe. This method could be applied conveniently, efficiently, and reliably to metabolome analysis for strict anaerobes in air. Biotechnol. Bioeng. 2014;111: 2528–2536. © 2014 Wiley Periodicals, Inc.